ZinjaI: an integrated development environment for a first programming course with C++ - Novara, Pablo (2009)
Most of the students in Argentinian universities tends to experience huge adaptation problem over their first year. It is the main cause for very high indexes of abandonment. In the case of computing/informatics systems careers, in the first programming course, the students must learn a series of concepts related to computing algorithms abstraction, programming language syntax and the real implementation of programs using C++. It is a known fact that this is a cryptic language for the beginner programmer, and usually the very complex Integrated Development Environments (IDE) existing today are not designed to solve this particular issue. Instead, the software seem to be an additional handicap. ZinjaI is a new IDE for writing C++ programs developed with student's needs in mind, with powerful features for making design, edition, debugging and logic tracing of programs simpler tasks. The utilization of this tool in several first year cohorts seems to make a significant improvement for the learning process.